Association between bacterial vaginosis or chlamydial infection and miscarriage before 16 weeks' gestation: prospective community based cohort study. Issue 7376 (7th December 2002) - Oakeshott, Pippa; Hay, Phillip; Hay, Sima; Steinke, Frances; Rink, Elizabeth; Kerry, Sally
Abstract: Objectives: To assess whether bacterial vaginosis or chlamydial infection before 10 weeks' gestation is associated with miscarriage before 16 weeks. Design: Prospective cohort study. Setting: 32 general practices and five family planning clinics in south London. Participants: 1216 pregnant women, mean age 31, presenting before 10 weeks' gestation. Main outcome measure: Prevalence of miscarriage before 16 weeks' gestation. Results: 121 of 1214 women (10.0%, 95% confidence interval 8.3% to 11.7%) miscarried before 16 weeks. 174 of 1201 women (14.5%, 12.5% to 16.5%) had bacterial vaginosis. Compared with women who were negative for bacterial vaginosis those who were positive had a relative risk of miscarriage before 16 weeks' gestation of 1.2 (0.7 to 1.9). Bacterial vaginosis was, however, associated with miscarriage in the second trimester at 13-15 weeks (3.5, 1.2 to 10.3). Only 29 women (2.4%, 1.5% to 3.3%) had chlamydial infection, of whom one miscarried (0.32, 0.04 to 2.30). Conclusion: Bacterial vaginosis is not strongly predictive of early miscarriage but may be a predictor after 13 weeks' gestation. The prevalence of Chlamydia was too low to assess the risk, but it is unlikely to be a major risk factor in pregnant women.